Problems and Complications During the Treatment of Infertility in Women with Polycystic Ovary Syndrome - Müberra Namlı Kalem; Ziya Kalem; Timur Gürgan (Medical Network, 2016)
Polycystic ovary syndrome (PCOS) is the most frequent endocrine disorder existing in women in their reproductive years and it is one of the most evaluated and discussed subjects of reproductive medicine with regard to its diagnosis and treatment. Patients with PCOS constitute the most difficult population in the management of infertility. The factors that increase the success rates in the treatment of PCOS infertility are: pretreatment changes in life style, dietetic and psychological support, a detailed evaluation of the couple and the appropriate selection of the treatment protocol, a wide-spectrum approach to maintaining ovarian and endometrial synchronization in the management of the cycle, and well-developed laboratory conditions to support embryonic quality. However, even if these conditions are provided, OHSS, cancellations of the cycle, poor oocyte, and embryo qualities, unsuccessful fertilization and implantation, chromosomal abnormalities and early losses may still be experienced.